An Extremely Rare Case of Anomalous Left Main Coronary Artery Originating From Single Right Coronary Ostium Managed Using Heart Team Approach - Akbar, Hina (Cureus, 2020)
Anomalies of coronary artery origin are rare, difficult to diagnose using conventional testing methods and extremely challenging to eventually manage once diagnosed. The risk of adverse outcomes increases as such patients age and develop atherosclerosis in such vessels. A comprehensive and multidisciplinary approach may be required to best manage such difficult cases.  We present a case of a 65-year-old female with symptoms of chest pain concerning for unstable angina. She also complained of occasional diaphoresis and dizziness. Physical examination revealed a regular heart rhythm with no vascular bruits. An electrocardiogram (EKG) only showed normal sinus rhythm and left axis deviation. Non-invasive testing included an echocardiogram, which showed multiple wall motion abnormalities. A diagnostic cardiac catheterization via right radial artery approach was performed to delineate her coronary anatomy and rule out ischemic etiology. This led to diagnosis of anomalous coronary anatomy with an anomalous left main coronary artery from single right coronary ostium. Furthermore, it showed significant obstructive multi-vessel coronary artery disease involving distal left main artery, proximal left anterior descending artery, left circumflex and right coronary arteries. The patient had a right dominant system with absent left coronary cusp. Percutaneous vs surgical revascularization options were considered. Given high Syntax score and acceptable Society of Thoracic Surgeons (STS) risk, Heart Team approach was pursued and the patient was referred for multi-vessel surgical revascularization.